The Nanotechnology: An applied and extensive approach in solving crimes: Dr. Syeda Mona Hassan, Dr. Aftab Ahmad Malik - Dr. Syeda Mona Hassan; Dr. Aftab Ahmad Malik (International Journal for Electronic Crime Investigation, 2022)
Nanotechnology has great influence on modern technology. In order to identify, individualize, andassess evidence, forensic science applies knowledge and methods. Then, with the aid of evidence,crime scenes will be rebuilt, investigations will be directed, and offenders will be prosecuted.Nano-analysis is one of modern technology that is most frequently used in forensic science. Thecharacterization can be done by using tools like the atomic force microscope (AFM), aman microspectroscopy, scanning electron microscope (SEM), and transmission electron microscope (TEM)(Micro-Raman). Nanotechnologies might be essential in current forensic investigation issues likeforensic toxicological analysis, explosive detection, detection of explosive residue, finger printanalysis, forensic DNA analysis, forensic nano trackers, and drug-facilitated crime.